Gradient‐induced vibrations and motion‐induced Lenz effects on conductive nonmagnetic orthopedic implants in MRI - Zilberti, Luca; Curreli, Cristina; Arduino, Alessandro; Zanovello, Umberto; Baruffaldi, Fabio; Bottauscio, Oriano (Magnetic resonance in medicine, 2025)
Purpose To quantify the extent of gradient‐induced vibrations, and the magnitude of motion‐induced displacement forces (“Lenz effect”), in conductive nonmagnetic orthopedic prostheses. Methods The investigation is carried out through numerical simulations, for a 3 T scanner. For gradient‐induced torques and vibrations, a knee and a shoulder implant are considered, at dB/dt equal to 42 T/s (rms). For motion‐induced forces associated with the Lenz effect, a knee and a hip implant are studied, considering a patient who translates on the examination couch, or walks next to it. Results Gradient‐induced torques may be within the same order of magnitude as the worst case gravitational torque defined in the ASTM standards. However, for all investigated cases, they result to be lower. In vacuum, the extent of the corresponding vibration reduces with frequency. At the lowest investigated frequency (270 Hz), it keeps below 25 μm. For an implant partially embedded in bone, the extent of the vibration increases with frequency. Nevertheless, the displacement is far lower than the worst case observed in vacuum (negligible in contact with the bone; ˜1 μm or less where the implant emerges from the bone). The Lenz effect induced by the motion of the patient through the stationary magnetic field produces forces on the order of a few millinewtons (i.e., at least two orders of magnitude lower than the implant weight). Conclusion Comparing the results with mechanical loads caused by ordinary activities of daily living, and with the levels of tolerable micromotions, a good safety margin is confirmed.